Implementation of Pancasila Values in an Effort to Build Tolerance Attitudes in Students - Kifah Mahmudah; Adina Vivia Wijaya; Tri Amalia Amnas; Jamilatul Mahdiyah (CV. ITTC INDONESIA, 2025)
Pancasila, as the foundation of the Indonesian state, has an important role in building tolerance, especially among students. In a multicultural society, tolerance is the main key to creating harmony and productive diversity. The values of Pancasila, such as social justice and unity, can be applied in daily life to strengthen mutual respect between individuals from various religious, ethnic, and cultural backgrounds. This research uses the literature study method to analyze the implementation of Pancasila values in building tolerance among university students. The results show that the understanding and application of Pancasila values can increase students' awareness of the importance of tolerance in maintaining social harmony. Thus, Pancasila not only functions as an ideological foundation, but also as a guideline in building a strong attitude of tolerance among the younger generation.